A difficult case of Austrian syndrome: a case report - Sonia Peribáñez; Iván De María-Mier; Diana Batin; Mario Martínez-Fleta; Marta Antonio-Martín; Carmen Aured-Guallar; José M. Vallejo-Gil; Alexander S. Vaca-Núñez; Rosa M. Martínez-Álvarez; Ruth Caballero-Asensio (The Egyptian Heart Journal)
Abstract Background The Austrian syndrome is a rare but malignant triad consisting of pneumonia, meningitis, and endocarditis caused by an invasive pneumococcal infection, with a mortality rate of approximately 32%, rising to over 60% if not diagnosed early. Most of the knowledge about this rare disease comes from case reports. The uniqueness of this case lies in the late presentation of endocarditis. Case presentation A 59-year-old woman with a medical history of hypertension, dyslipidemia, hypothyroidism, and mesangial proliferative glomerulonephritis was admitted to our hospital with meningitis and pneumonia with bacteremia caused by Streptococcus pneumoniae. After receiving antibiotic treatment, the patient improved, and an echocardiogram was performed, ruling out endocarditis. She was discharged and readmitted three weeks later due to endocarditis with an acute perforation of the aortic valve, which required urgent surgery. Fortunately, the patient survived. Conclusion In cases of invasive pneumococcal disease with involvement of more than one focus, the possibility of developing infective endocarditis should be considered, especially in cases of hemodynamic instability or heart failure. The Austrian syndrome is a triad that should not be overlooked due to its high mortality rate, especially the possibility of the late onset of endocarditis.